Just War contra Drone Warfare - Hall, Joshua M. (Conatus - Journal of Philosophy, 2023)
In this article, I present a two-pronged argument for the immorality of contemporary, asymmetric drone warfare, based on my new interpretations of the just war principles of “proportionality” and “moral equivalence of combatants” (MEC). The justification for these new interpretations is that drone warfare continues to this day, having survived despite arguments against it that are based on traditional interpretations of just war theory (including one from Michael Walzer). On the basis of my argument, I echo Harry Van der Linden’s call for “an international treaty banning all weaponized UAV [uninhabited aerial vehicles].”